Doing good while making money: Individual investor participation in socially responsible corporations. Issue 8 (18th September 2017) - Chakrabarty, Bidisha; Lee, Sang Bong; Singh, Nitish
Abstract : Purpose: The purpose of this paper is to examine the performance of exchange traded funds (ETFs) that hold corporate social responsibility (CSR) stocks and compare their risk-return characteristics with the market. Design/methodology/approach: The authors use the Sharpe ratio and Jensen's α from multivariate regressions to perform a multi-country study to examine how CSR-oriented ETFs perform against global, national, and regional market indexes. The authors examine paired groupings of each CSR-oriented ETF with its corresponding index after appropriate risk adjustments. Findings: The authors find that CSR-oriented ETFs' perform similar to their market indexes. Thus, individual investors can earn comparable returns while investing in CSR-oriented ETF, indicating that they can indeed do "good" while not missing out on returns. However, the authors also find that unlike the previously documented buffer effects that CSR-oriented firms enjoy, CSR-oriented ETFs do not outperform their market indexes during economic downturns. Thus, CSR-oriented ETFs are not safe havens for individual investors during times of economy-wide slumps. Research limitations/implications: The main limitation of this study is its limited sample size. Because the authors use novel hand-collected data, the authors have 11 CSR-focused ETFs with their corresponding indexes. Originality/value: To the authors' knowledge, this is the first study that examines individual investor participation using CSR-oriented ETFs. The study is made possible by hand-collected data on CSR-related ETFs which identify in detail the composition of each of these ETFs, and the findings highlight how individual investors can promote CSR while also making sound investments.